Phosphonate and Bisphosphonate Inhibitors of Farnesyl Pyrophosphate Synthases: A Structure-Guided Perspective - Park, Jaeok; Pandya, Vishal R.; Ezekiel, Sean J.; Berghuis, Albert M. (Frontiers in Chemistry, 2021)
Phosphonates and bisphosphonates have proven their pharmacological utility as inhibitors of enzymes that metabolize phosphate and pyrophosphate substrates. The blockbuster class of drugs nitrogen-containing bisphosphonates represent one of the best-known examples. Widely used to treat bone-resorption disorders, these drugs work by inhibiting the enzyme farnesyl pyrophosphate synthase. Playing a key role in the isoprenoid biosynthetic pathway, this enzyme is also a potential anticancer target. Here, we provide a comprehensive overview of the research efforts to identify new inhibitors of farnesyl pyrophosphate synthase for various therapeutic applications. While the majority of these efforts have been directed against the human enzyme, some have been targeted on its homologues from other organisms, such as protozoan parasites and insects. Our particular focus is on the structures of the target enzymes and how the structural information has guided the drug discovery efforts.